The behaviour of normal concrete containing POFA as partial fine aggregate replacement - Maizatil Akma, Yaacob (2016)
Nowadays, demand for sand and gravel continues to increase in concrete production. Excessive sand mining has negative effect to environment setting and water quality of the river basin. At the same time, Malaysia as one of the largest palm oil producer generates abundant palm oil fuel ash, a by-product from palm oil mill which dumped as waste. Palm oil fuel ash (POFA), produced by burning palm oil shell and husk as fuel ash in a palm oil mill boiler to generate electricity for the palm oil extraction process. Utilization of POFA can reduce amount of waste ending at landfill that contribute to the environmental problem and reduce the cost of concrete. In this study, the effect of POFA content as partial fine aggregate replacement on fresh properties and compressive strength on normal concrete has been investigated. There were six types of mix have been used in this study. Concrete mixes containing 0%, 2%, 4%, 6%, 8% and 10% of POFA fine aggregate replacement level were cast before subjected to water curing for 7, 14 and 28 days. Workability test, compressive strength test and water absorption were conducted for the concrete. The findings show that inclusion of 6% POFA enhances the compressive strength performance of concrete.